Development of native and introduced tree species under two water regimes in Acaraú, Ceará - José Dionis Matos Araujo; João Alencar de Sousa; Alisson Moura Santos; Diva Correia; Antonio Marcos Esmeraldo Bezerra (Revista Ciência Agronômica)
ABSTRACT The aim of this study was to evaluate development in the following tree species: Acacia mangium Willd, Anadenanthera colubrina var. cebil (Griseb.) Altschu, Casuarina equisetifolia L. ex J. R. Forst. & G. Forst, Handroanthus impetiginosus (Mart. Ex DC.) Mattos, and Colubrina glandulosa subsp. reitzii (M.C.Johnst.) Borhidi under two water regimes in the Irrigated Perimeter of Baixo Acaraú, in the state of Ceará. The experiment was conducted over seven years, with the factors represented by water regimes, species and periods in an arrangement of split-split plots in a completely randomised design repeated over time with four replications of two plants each. The response variables were total height, diameter at breast height, volume, absolute growth rate in height and diameter, and current and average annual increase in volume. After seven years, the species Acacia mangium, Casuarina equisetifolia, Handroanthus impetiginosus, Anadenanthera colubrina and Colubrina glandulosa presented the following respective mean volumes: 0.62, 0.47, 0.45, 0.31 and 0.29 m3 irrespective of the water regime. Despite a reduction in the growth rates of the species during each period, they remained positive, and growth did not stop. The mean values for volume confirm that the species showed similar growth for the water regimes under study. An irrigated regime of up to one year is therefore suggested for cultivating these species in the Irrigated Perimeter of Baixo Acaraú, Ceará.